Colloidal Synthesis of Bulk-Bandgap Lead Selenide Nanocrystals - Abeywickrama, Thulitha M.; Hassan, Asra; Snee, Preston T. (Frontiers in Chemistry, 2018)
Lead selenide quantum dots (QDs) are low-bandgap IV-VI semiconducting nanomaterials that have been studied for a variety of applications. Their preparation using colloidal methods can produce small spherical to larger cubic nanocrystals, with an upper limit of ~17 nm reported to date. Here we describe methods for preparing cubic PbSe nanocrystals over a 20→40 nm size range using a twostep procedure. Specifically, ~10 nm PbSe QDs are generated using the rapid injection method, the products from which are overcoated with additional lead and selenium precursors. The use of two lead reagents were studied; lead oleate resulted in a maximum of 20 nm cubes, while more reactive lead hexyldecanoate resulted in much larger nanomaterials with bulk bandgaps. However, PbSe samples prepared with lead hexyldecanoate also contained agglomerates. Special care must be taken when characterizing larger strained nanomaterials with X-ray powder diffraction, for which the Scherrer equation is inadequate. A more rigorous approach using the Williamson-Hall method provides characterizations that are consistent with electron microscopy analysis.